Austrian Social Security Database - Josef Zweimüller; Rudolf Winter-Ebmer; Rafael Lalive; Andreas Kuhn; Jean-Philippe Wuellrich; Oliver Ruf; Simon Büchi (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
The Austrian Social Security Database (ASSD) is a matched firm-worker data set, which records the labor market history of almost 11 million individuals from January 1972 to April 2007. Moreover, more than 2.2 million firms can be identified. The individual labor market histories are described in the follow- ing dimensions: very detailed daily labor market states and yearly earnings at the firm-worker level, together with a limited set of demographic characteris- tics. Additionally the ASSD provides some firm related information, such as geographical location and industry affiliation. This paper is a short description of this huge data base and intended for people using this data in their own empirical work.
Keywords: 330